Time series of water parameters, nutrient, and gas samples in the Coffs Creek estuary, March 2018 - Rebecca Woodrow (PANGAEA, 2021)
Measurements of water parameters of temperature, dissolved oxygen, and salinity as well as nutrient samples of dissolved organic carbon, filtered and unfiltered nitrogen, and nitrous oxide were collected through time series apparatus, hourly and 3 hourly, over 185 hours and exclusively at one site in the lower estuary (Site 1). A calibrated Hydrolab MS5 sonde measured and logged water temperature (±0.02°C), DO (±0.2 mg/L), and salinity (±0.02) at 30 m intervals and a depth logger (CTD diver) measured water depth in 15-minute intervals. Nutrient samples (including duplicates), filtered and unfiltered, were collected with a sample-rinsed 60 mL polyethylene syringe. Samples for dissolved organic carbon (DOC) analysis were filtered using pre-combusted 0.7 μm GF/F filters (Whatman), into 40 mL borosilicate vials (USP Type I). Samples for nitrogen were immediately filtered using Satourious ™ 0.45μm cellulose acetate syringe filters into 10 mL polyethylene sample tubes. All samples were kept in a cold icebox, away from light, for less than 5 hours and then frozen until laboratory analysis. Nutrient analysis of DOC was performed with the 40 mL borosilicate vials (USP Type I) first treated with 30 μL of H3PO4 before analysis using an Aurora 1030W TOC Analyser (Thermo Fisher Scientific, ConFLo IV). Nutrient analysis of ammonium (NH4+), NOx (nitrate plus nitrite), and total dissolved nitrogen (TDN) was performed on the 10 mL polyethylene sample tubes colourimetrically using a Lachat Flow Injection Analyser. Total dissolved nitrogen and dissolved inorganic nitrogen were calculated from the nitrogen samples. N2O samples were collected from a time series gas equilibration device via a one-way valve into 150 mL syringes then transferred from the syringes into a Supelco company 1 L gasbag. A total of 800 mL of gas was taken per sample. The gasbags were analysed for N2O using cavity ringdown spectroscopy on a calibrated Picarro G2308.
In: Woodrow, R (2021): Water parameters, nutrient, and gas samples in the Coffs Creek estuary, 2017-2018 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937740